Pengembangan Sumber Daya Manusia dan Komitmen Organisasional terhadap Kinerja Karyawan PT. Sinar Terang Mandiri - Tumangken, Tirza G.; Areros, William A.; Rumawas, Wehelmina (JURNAL ADMINISTRASI BISNIS (JAB), 2020)
This study aims to see the effect of Human Resource Development and Organizational Commitment on Employee Performance at PT. Sinar Terang Mandiri Manado. This approach uses a quantitative approach, with a sample of 60 respondents. The results of this study also indicate that there is a positive and insignificant influence between Organizational Commitment on employee performance, meaning that the level of organizational commitment will affect the level of employee performance. Simultaneously, the development of Human Resources and Organizational Commitment is able to explain the influence on Employee Performance, the effect of Human Resource Development on Employee Performance of 3.102, the effect of Human Resource Development on Organizational Commitment of 4.327, and the effect of Organizational Commitment on Employee Performance of 1,529, the remaining data other variables outside this study.